2022
DOI: 10.1177/0193841x221120483
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Technology in Asian Economies: The Environmental Impact of Remittances and Economic Complexity

Abstract: In recent years, scholars have determined various determinants of environmental degradation using the panel and time-series studies. However, technological innovations (TI) and remittances, among the financial system’s essential components, are relatively ignored. In addition, nations’ economic progress and environmental performance also depend upon the nature of their economic structure. This empirical research investigates the effects of TI, remittances and economic complexity (EC) on CO2 controlling economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…All people in societies including businesses, farmers, the environment, and others, benefit from a circular economy. Similar findings confirming the positive role of economic complexity can be found in the literature for Asian countries (Liu et al 2022), G7 countries (Ghosh et al, 2022), regional comprehensive economic partnership (RCEP) countries (Bashir et al, 2022), and 20 emerging economies (Ahmad et al, 2021).…”
Section: Resultssupporting
confidence: 88%
“…All people in societies including businesses, farmers, the environment, and others, benefit from a circular economy. Similar findings confirming the positive role of economic complexity can be found in the literature for Asian countries (Liu et al 2022), G7 countries (Ghosh et al, 2022), regional comprehensive economic partnership (RCEP) countries (Bashir et al, 2022), and 20 emerging economies (Ahmad et al, 2021).…”
Section: Resultssupporting
confidence: 88%
“…Indeed, the extant literature suggests that there are various channels through which trade openness may infl uence the productive capacities of economies. For instance, trade openness can potentially expand the demand for domestic products, engender industrial and technological advancement, trigger higher economic productivity and fast income growth, as well as improve capital investment, economic sophistication and knowledge transfer (Liu et al, 2022;Ekeocha et al, 2021;Wiredu et al, 2020;WB, 2019;IMF, 2019).…”
Section: Evidence Of Linkage Between Trade Openness and Productive Ca...mentioning
confidence: 99%
“…Although studies continue to focus on CO 2 emissions (Jahanger & Usman, 2022; Liu et al, 2022, Suki et al, 2022; Zheng et al, 2022), recent literature has found EF to be a more comprehensive indicator for simultaneously assessing air, water, and soil pollution (Sharif et al, 2021, Pata & Hizarci, 2022). EF tracks the ecological assets needed to produce the natural resources consumed by humanity and sequester the waste.…”
Section: Literature Reviewmentioning
confidence: 99%